Differences between Arabic Antonym (Al-Taddad/ التضادّ) and Interpretation of the Qur'an - Nurus Syarifah (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2022)
This article examines antonyms in Arabic and the Al-Qur'an, which are kalamullah which were derived from Arabic. This research aims to explain the differences regarding what is meant by antonyms in Arabic rules and what is meant by antonyms which are agreed upon by the commentators in interpreting the Al-Qur'an. The method used in this research is descriptive analytical method. This method is used to parse the question, where are the differences between the antonyms in the Arabic norm and the interpretation of the Al-Qur'an? From this paper it can be concluded that antonyms in Arabic can be said to be more complex like other language rules. Starting from the definition, classification, linguist opinion about the existence of antonyms, to the reasons for their appearance, there are various differences of opinion between one another. While antonyms in the interpretation of the Al-Qur’an, the interpreters agree that what is called an antonym in interpreting the Al-Qur’an is what is called idiomatic in Arabic rules, namely one and the same word has opposite meanings depending on what words accompany it. Or what comes after.